RNA methodologies : a laboratory guide for isolation and characterization - Farrell, Robert E (ELSEVIER, 2010)
This is the fourth edition of the successful laboratory guide which has translated the rich story of riboneucleic acid for over fifteen years. RNA Methodologies 4e presents the latest collection of tested laboratory protocols for the isolation and characterization of eukaryotic and prokaryotic RNA with greater emphasis on transcript profiling, including quantification issues and elucidation of alternative transcription start sites. Collectively the chapters work together providing analysis with clear take-home lessons to assist researchers to understand RNA and to optimize time at the bench. The abundant use of flow charts, tables and graphs are especially helpful in the planning and implementation phases of a project and facilitate learning. 30% new material in this edition includes the addition of RNA isolation protocols including RNA isolation from tissue, expansion of PCR optimization analysis and RNA interference sections, the introduction of a new chapter dealing with the molecular biology of plants, and an expanded glossary.